Improvisasi Metode Biseksi pada Maximum Power Point Tracking (MPPT) dengan Menggunakan Algoritma Incremental Conductance - Habibi, Muhammad Nizar; Windarko, Novie Ayub; Efendi, Moh. Zaenal; Eviningsih, Rachma Prilian; Mahendra, Luki Septya; Junianto, Sony (ROTASI, 2024)
The solar energy potential reaches 207.8 GWp in Indonesia, providing numerous opportunities to harness renewable energy. One approach is utilizing solar panels; however, these panels have a low energy conversion rate. Maximum Power Point Tracking (MPPT) is a technique that can maximize the performance of solar panels to consistently generate maximum power. Bisection MPPT is implemented in the system due to its ease of implementation, but it performs less effectively under low irradiance. The Incremental Conductance algorithm is a suitable choice for improving Bisection MPPT. Apart from being easy to implement, the Incremental Conductance algorithm is not dependent on the characteristics of the solar panel. It also features Variable Step Size to eliminate ripple when reaching the maximum power of the solar panel. Incremental Conductance MPPT can enhance Bisection MPPT with a maximum increase of 17,483 Watts. The Bisection-Incremental Conductance MPPT algorithm takes 2.122 seconds to reach the maximum power of the solar panel, generating 1.89 x 10^6 Ws of energy for 0.4 seconds. It yields the highest value compared to Bisection MPPT and Incremental Conductance MPPT.